2016
DOI: 10.5005/jp-journals-10045-0035
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcome of Ectopic Pregnancy in a Tertiary Care Center

Abstract: Objective: To assess the results of management of ectopic pregnancy with respect to maternal morbidity and mortality and to analyze the risk factors. Materials and methods:Hospital based cross-sectional study of 52 patients who were diagnosed as ectopic pregnancy in the reproductive age group of 15 to 44 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In the nucleosome, two copies of histone H2A, H2B, H3, and H4 form a histone octamer, which is surrounded by DNA 147 base pairs long (Luger et al, 1997). The basic residues such as lysine and arginine in the N-terminal tail of each histone are covalently modified by acetylation to regulate the transcription of genes wrapped around the core histone (Srivastava, Singh & Dubey, 2016). Since a report that indicated that gene activity is related to histone acetylation, the modification of histone acetylation and deacetylation have received increasing attention (Grunstein, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In the nucleosome, two copies of histone H2A, H2B, H3, and H4 form a histone octamer, which is surrounded by DNA 147 base pairs long (Luger et al, 1997). The basic residues such as lysine and arginine in the N-terminal tail of each histone are covalently modified by acetylation to regulate the transcription of genes wrapped around the core histone (Srivastava, Singh & Dubey, 2016). Since a report that indicated that gene activity is related to histone acetylation, the modification of histone acetylation and deacetylation have received increasing attention (Grunstein, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In the nucleosome, two copies of histone H2A, H2B, H3, and H4 form a histone octamer, which is surrounded by DNA 147 base pairs long (Luger et al, 1997). The basic residues such as lysine and arginine in the N-terminal tail of each histone are covalently modified by acetylation to regulate the transcription of genes wrapped around the core histone (Srivastava, Singh & Dubey, 2016). Since a report that indicated that gene activity is related to histone acetylation, the modification of histone acetylation and deacetylation have received increasing attention (Grunstein, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In the nucleosome, two copies of histone H2A, H2B, H3, and H4 form a histone octamer, which is surrounded by DNA 147 base pairs long (Luger et al, 1997). The basic residues such as lysine and arginine in the N-terminal tail of each histone are covalently modified by acetylation to regulate the transcription of genes wrapped around the core histone (Srivastava, Singh & Dubey, 2016). Since a report that indicated that gene activity is related to histone acetylation, the modification of histone acetylation and deacetylation have received increasing attention (Grunstein, 1997).…”
Section: Introductionmentioning
confidence: 99%